LEOPARD syndrome. The first case reported in Saudi Arabia. - Shelleh, H.H.; Saleh, A.M.; Ibrahim, M.S.; Sumangala, B.; Dawood, S. (European Journal of Pediatric Dermatology, 2005)
We report on a 3-year-old Saudi boy who demonstrated lentigines, hypertrophic cardiomyopathy, ocular hypertelorism and deafness, thus fitting the diagnosis of LEOPARD syndrome or Multiple Lentigines Syndrome. It was a sporadic case. The patient manifested almost all the clinical features included in the acrostic LEOPARD except A "abnormality of genitalia" which might appear later, and P "pulmonary stenosis" which was replaced by hypertrophic cardiomyopathy. Lentigines were the clue sign leading to the diagnosis. The child was missed for follow up, to expire suddenly at the age of 8 years as we knew later. This case from the south of Saudi Arabia documents the presence of LEOPARD syndrome in this region, and is thought to be the first Saudi LEOPARD reported. Patients with early onset LEOPARD syndrome have a poor prognosis owing to the rapid progression of the cardiac lesion, thus they should be followed up carefully to avoid the fatal complications. We would like to remind that lentigines should not be clinically neglected, because they may serve as a clue of catastrophic syndromes.